Finite-element simulation for contribution of matric suction and friction angle to stress distribution during pulling-Out process - Khalilnejad, A.; Ali, F.H.; Hashim, Roslan; Osman, N. (2013)
In slope engineering, soils are ordinarily in an unsaturated state. Today the application of unsaturated soil mechanics theory to slope stability analysis has become an essential point in geotechnical engineering research. To explain the relationship between matric suction and soil structure with slope stability (via the pulling-out effect), reasonable finite-element (FE) modules can be created. By using FE analysis (which includes the existing soil parameters), the stability of residual soil slope can be simulated under different water contents (via changes in matric suction) and soil structures (via differentFvalues). Inferring from the soil-water characteristic curve obtained from previous work, the influence of matric suction on unsaturated soil slope is determined. The importance of matric suction and soil structure is discovered during the root pulling-out analysis. The results show that because of increasing matric suction in unsaturated soil (which is the result of the decreasing degree of saturation), the required force during the pulling-out process (root anchorage) and consequently stress-distribution capacity will be increased, and the safety factor of the soil slope is amended. However, changes in soil friction angle do not affect root anchorage in roots with a sharp deviation angle (53Â°); for a root with a steep deviation angle (15Â°), as the soil structure improves by means of increases in the internal friction angle, the forces needed to determine the pull out angle, and accordingly, the stress-distribution capacity, are modified, and the safety factor is improved.